Effect of clove cigarette exposure on white rat : special emphasis on the histopathology of respiratory tract (Medical Journal of Indonesia, 2007)
Cigarette smoke is proved to cause various disturbances on respiratory tract. Clove cigarette is far more dangerous than common ("white") cigarette, since the tar, nicotine, and carbon monoxyde content is significantly higher. In Indonesia, 88% smokers consume clove cigarette. The clove cigarette effect to the respiratory tract have never been studied. Aim of this research is to study histopathological changes of respiratory tract in Sprague-Dawley white rats after smoke cigarette exposure. The study was performed using 20 white rats starting September 2005 until May 2006. Necropsy was done after final day of smoke exposure, then histopathological slides of the respiratory tract were processed and stained under light microscope and videomicrometer. Observed parameters were height and number of ciliated epithelia and goblet cells, also number of pneumocytes types I, II, and macrophages, and interstitial lung tissue reactions. The latest parameters were observed with semi-thin sections of resin embedded lung stained with Toluidine Blue. Result showed considerable histopathological changes on respiratory tract. The amount of epithelial cells on the group exposed to clove cigarette smoke were significantly higher than control group (P<0.05) on sinus, bronchi, and bronchioli area, while no significant difference were found on trachea (P>0.05). Number of goblet cells in exposed group was also higher (P>0.05). The epithelial height in exposed group was higher compared to control, but no statistical differences were found between male and female rats. The interstitial pneumonia score was statistically different (P<0.05) between the two groups. The amount of pneumocytes type II was higher than types I within the exposure group. Based on all mentioned above, we suggest that clove cigarette smoke exposure causes pathological disorders in rat respiratory tract. (Med J Indones 2007; 16:212-8)